„Bijący talent dramatyczny”? Wokół emigracyjnej recepcji Towarzysza Października Kazimierza Wierzyńskiego - Osiński, Jakub (Tematy i Konteksty, 2018)
The paper is devoted to the one and only drama of Kazimierz Wierzyński (1894–1969) ‘Comrade October’, written in 1950, and released only in 1992. Its aim is to explain why it was not published immediately after the writing. The author attempts to reconstruct the circumstances of the creation of the work and to effort to publish and exhibit it, as well as to present the state of research. He show the ‘Comrade October’ against the background of emigratory dramaturgy and theater life, which serves to reflect on the political character of the drama and to analyze the reception of his public readings in èmigrè circles (Theatre ‘Pro Arte’ by Olga Żeromska, 1954).